Political institutions and government spending behavior in Iran - Sajjad Faraji Dizaji; Mohammad Reza Farzanegan (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This study examines how quality of political institutions affects the distribution of government budget and how development of government spending in major sections shapes the political institutions in Iran. This question has become especially important due to recent international sanctions, aiming to change the political behavior of Iran. We use the impulse response functions (IRF) and variance decomposition analysis (VDC) on the basis of Vector Autoregressive (VAR) model with annual data from 1960 to 2006. Our results show the importance of political institutions in patronage and public goods provision spending in Iran. The results imply that a shock in positive changes of democratic quality of institutions leads to negative and statistically significant response of military spending and positive and statistically significant response of education expenditures in short term. If sanctions are successful to change the political behavior of Iran in short run (Dizaji and Bergeijk, 2013), then one can also expect to see a reduction in allocated budget for military in Iran.
Keywords: H11; H41; P16; O53; O43; 330; political institutions; government spending; Iran; VAR modelling; sanctions